Technical Note: Torsional Analysis of Steel Sections - Moore II, William E.; Mueller, Keith (Engineering Journal, 2002)
Torsional analysis of rolled steel sections is generally accomplished with torsional function curves which have been published by the American Institute of Steel Construction in Design Guide No. 9, Torsional Analysis of Structural Steel Members (Seaburg and Carter, 1997), which is an update to an earlier Bethlehem Steel publication (Heins and Seaburg, 1963). Such problems are more easily solved with a personal computer than with charts, and this paper presents the equations in a form suitable for programming.